An analytical study of social skills and their relationship to the levels of sports culture according to the variable of training age of first-class football players for the 2020-2021 season - Ahmed, H. O. (Journal of Human Sport & Exercise, 2021)
Social skills are all the skills that can be acquired and that determine the strengths of a person, personal skills are divided into two parts, which are technical skills, those are skills related to activity and work and social skills, that relate to the personal advantages of a person, and all the methods of communication through which the individual works. It should be noted that success in this matter is achieved by communicating with other parties, and it is better for a person to be successful in those relationships with other parties, whether co-workers, friends and those around him in general. Social skills have become today in circulation in all areas of life and work to develop and grow up them by specialists that lead To increase interaction between individuals and groups within their societies and to move to higher levels despite the different opinions and trends regarding the multiplicity of these skills, The importance of research that whenever players perfected social skills with possessing a culture of physical skills according to training age to the players, which is an important factor in mastering the skill associated with the sports culture, The researcher used the descriptive methodology. The survey method and relationships Relational more appropriate to the of the problem nature and achieve the goals of research. Where the research sample was intentionally determined and they are 200 (players) first-class players for the southern region of football officially registered in the Iraqi Football Association lists representing eight clubs, where 10 players were excluded because of the inability to communicate with them due to injuries, and thus the actual research sample constituted 190 players who make up 95% of the original community for the research, and the most prominent conclusions are: The emergence of different levels in the results of the athletic Culture Scale of the research sample, and the highest percentages were within a good and very good. The emergence of different levels in the results of the social skills scale of the research sample, and the highest percentages were within a good and very good.